Beliefs of Bangsamoro Madaris Learners About Language Learning and their Relationship with Academic Performance - Abdullah Karim, Kurais (2008)
This study investigated the beliefs about language learning of 100 Bangsamoro Madaris learners in Southern Philippines. The survey instrument, ‘Beliefs About Language Learning Inventory’ or BALLI (Horwitz 1987) which included 34 items on a Likert-type scale, was used to collect data on the learners’ beliefs about English language learning. The primary aim was to describe their beliefs about English language learning, which to date, has remained unexplored. The second aim was to explore the relationship between their beliefs and academic performance represented by their final grades in English subject in order to provide empirical backing of the relationship, otherwise lacking in beliefs literature (Peacock, 1999). Aside from that, the beliefs of the respondents towards Arabic language learning were gathered using a modified BALLI in order to compare their beliefs about Arabic language learning to their beliefs about English language learning. Findings of the descriptive analysis on the responses to BALLI statements indicate several firmly held beliefs among the respondents with varying degrees of validity.Some of the beliefs identified having important teaching implications are the importance given to excellent pronunciation, grammar and vocabulary. Respondents are also highly motivated and optimistic. The Pearson Product Moment correlation analysis between the beliefs and the final scores indicates relationship in five belief items, two of which different from previous studies (Peacock, 1999) which supports to the context specificity of beliefs. Finally, nine out of 21 statements compared in BALLI English and BALLI Arabic through t-tests are found significantly different, providing more evidence of the influence of social and cultural contexts in shaping beliefs.